Complications of Contact Lenses; A Clinico-experimental Study to Evaluate the Effects of Bacterial Contamination - Muhammad Ijaz Ahmad, Yousef Homood Aldebasi, Salah Mesalhy Aly (Pakistan Journal of Ophthalmology, 2013)
Purpose: To diagnose the complications and to study the effects of isolated bacteria from contact lens users on rabbit eyes. Material and Methods: A total of 100 contact lens wearers were subjected to clinical examinations. Contact lenses/or corneal swabs from 100 patients were collected for bacteriological examinations. The isolated bacteria were tested for pathogenicity through experimental study that was conducted on rabbits with the aid of clinical, serum biochemistry and histopathological examinations. Results: Among the 100 contact lens users, 23 were men and 77 women. The mean age was 21 years. Clinical examination revealed keratitis in 52% of contact lenses users, out of that 48% showed corneal infiltrates and 4% exhibited superficial corneal ulcer. Corneal abrasions, giant papillary conjunctivitis (GPC) and increased limbal neovascularization were found in 8, 10 and 6% of cases; respectively. In addition to this, nonspecific complications were found in 24% of cases. Lab investigations of the 100 collected contact lenses/corneal swabs revealed bacterial isolates from 28 samples. The isolated bacteria were identified as Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumonia from 7, 3, 10, 2 and 2 cases respectively and their antimicrobial sensitivity was done whereas multiple bacteria were detected in 4 samples. In parallel to the above study, the induced experimental eye infection of rabbits was performed which showed corneal abscess and corneal ulcers in case of Pseudomonas aeruginosa and Staphylococcus aureus induced corneal ulcers and clinical picture of the patients who proved culture positive results for pseudomonas aeruginosa and staphylococcal aureus was worse as compared to other patients. E coli or Klebsiella pneumonia developed macular and leucomatous types of corneal opacities. The infected rabbits showed varied biochemical changes regarding urea, creatinine and uric acid levels and the rabbits infected with pseudomonas aeruginosa showed almost double increase of serum uric acid level (p?0.05). Conclusion: Keratitis was the most predominant complication among contact lens users. Contact lens over wear, overnight wear and poor hygiene are the common causes of contact lens complications. Proper contact lens care and regular follow-up visit are essential for patient safety and wearing success.